TRAINING AND DEVELOPMENT (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Every individual is unique and has infinite  potentials. However such potential remains  untapped it we do not garner them rightfully.  Talents can be aptly used when the right  environment is created and necessary capacity  building measures are adopted to nurture  them. Among the numerous measures that can  be adopted, conducting trainings to enhance  knowledge level, skills and competency of  employees are significant. A new book entitled ‘TRAINING AND DEVELOPMENT’ by  Nishant Uppal has arrived on the shelf. It is  published by Pearson Education, India. A  succinct discourse on the book entails merit  from the perspective of many stakeholders. The book contains a total of seven chapters.  The first chapter gives an overall idea to the  reader on the general topic of the book and  is named as ‘Introduction to the Concept  of Employees Training and Development’.
Keywords: infinite; TRAINING; DEVELOPMENT